Cytomegalovirus Infection May Trigger Adult-Onset Still's Disease Onset or Relapses - Jia, Jinchao; Shi, Hui; Liu, Mengguo; Liu, Tingting; Gu, Jieyu; Wan, Liyan; Teng, Jialin; Liu, Honglei; Cheng, Xiaobing; Ye, Junna; Su, Yutong; Sun, Yue; et al. (Frontiers in Immunology, 2019)
Previous studies have revealed that several micro-organisms, especially DNA viruses, have been associated with adult-onset Still’s disease (AOSD). However, there are no studies on the relationship between the presence of viral infections in AOSD patients with disease occurrence and reactivation. In the present study, we aimed to investigate the presence of antibodies against virus, virus DNA load and nucleic acid sensors in AOSD patients. Anti-viral antibodies were measured by enzyme-linked immunosorbent assay (ELISA) in plasma samples from 100 AOSD patients and 70 healthy controls (HCs). The copy number of cytomegalovirus (CMV) DNA in 100 AOSD patients was detected by PCR. The expression levels of nucleic acid sensors interferon gamma-inducible protein 16 (IFI16) and absent in melanoma 2 (AIM2) in peripheral blood mononuclear cell (PBMC) and skin from AOSD patients and HCs were analyzed by PCR and immunohistochemistry. The levels of antibodies against CMV were significantly higher in AOSD patients compared to HCs. Moreover, the level of anti-CMV IgM antibody was significantly increased in patients with fever, sore throat, arthralgia and rash. CMV DNA was found in plasma of AOSD patients with disease new-onset and relapse. Furthermore, the copy number of CMV DNA significantly increased in patients with fever, sore throat, arthralgia and rash. And the significant associations of the CMV DNA level with the levels of leukocytes, erythrocyte sedimentation rate (ESR), C-reactive protein (CRP) and tumor necrosis factor-α (TNF-α) were observed. Moreover, we found an upregulation of cytoplasmic DNA-sensing receptor IFI16 and AIM2 in PBMC and skin from AOSD patients. In conclusion, our results showed that CMV infection may play a role in the initiation or amplification of inflammatory responses in AOSD.